(3GecGfGJ hecGfI GdMQjI hGdOjebQGWjI aj GdeTQhY GdfgVhj GdYQHj GdQGgf (B"(3QDjI GSJTQGajI(B"/ s - Zraik, Burhan ((3OeTb; s (3OGQ YdGAGdOjf; s, 2008)
Title translation: The potential and position of freedom and democracy in the current Arab renaissance project: (3z(BA forward-looking vision(3y(B. Author: Burhan Zurayks
Arabic
Keywords: Democracy-- Potential; JA71-80 Political Science- Theory. Relations to other subjects; Syria